An energy-efficient 2.5D through-silicon interposer I/O with self-adaptive adjustment of output-voltage swing - Xu, Dongjun (2015)
A self-adaptive output swing adjustment is introduced for the design of energy-eﬃcient 2.5D through-silicon interposer (TSI) I/Os. Instead of transmitting signal with large voltage swing, Q-learning based self-adaptive adjustment is deployed to adjust I/O output-voltage swing under constraints of both power budget and bit error rate (BER). Experimental results show that the adaptive 2.5D TSI I/Os designed in 65nm CMOS can achieve an average of 13mW I/O power, 4GHz bandwidth and 3.25pJ/bit energy eﬃciency for one channel under 10−6 BER, which has 21.42%reduction of power and 14.47% energy eﬃciency improvement.